Historical origins of welfare and social protection for women in Europe and the United States – since the end of the nineteenth century to the forties of the twentieth century - Baptista, V.; Marques Alves, P. (44th Annual Conference of the Social History Society, 2020)
In this paper we aim to analyse the contexts of the historical origins of the welfare state, highlighting women workers in social protection. Our objective is to understand the social policies in the maternal and child areas, inserted in assistance and social security. In France the expression "État-Providence" appeared in 1864, used with suspicion due to the growing intervention of the State. In this line it will be used in Portugal in the beginning of the twentieth century. On the other hand, in England the expression appeared in the context of World War II, with the social security directed to the whole population. In the United States the term Social Security was first used by President Franklin Roosevelt in 1935. In the definition of Welfare States, feminists point out that the role of women in guaranteeing the well-being of the family has not been developed. We found that countries such as Portugal women had fundamental roles in family care and protection. We will raise the following questions: Are the origins of the welfare state based solely on the situation of the man breadwinner? What was the social protection for single women workers with children? We want to demonstrate that the concept of gender and the role of the women's movement in these countries have contributed to a new conception and action of the welfare state.